ANTIHYPERGLYCEMIC ACTIVITIES OF LEAVES OF THREE EDIBLE FRUIT PLANTS (AVERRHOA CARAMBOLA, FICUS HISPIDA AND SYZYGIUM SAMARANGENSE) OF BANGLADESH - Shahreen, Shejuty; Banik, Joyanta; Hafiz, Abdul; Rahman, Shahnaz; Zaman, Anahita Tanzia; Shoyeb, Md. Abu; Chowdhury, Majeedul H; Rahmatullah, Mohammed (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Averrhoa carambola L. (Oxalidaceae), Ficus hispida L.f. (Moraceae), and Syzygium samarangense (Blume) Merr. & L.M. Perry (Myrtaceae) are three common plants in Bangladesh, the fruits of which are edible. The leaves and fruits of A. carambola and F. hispida are used by folk medicinal practitioners for treatment of diabetes, while the leaves of S. samarangense are used for treatment of cold, itches, and waist pain. Since scientific studies are absent on the antihyperglycemic effects of the leaves of the three plants, it was the objective of the present study to evaluate the antihyperglycemic potential of methanolic extract of leaves of the plants in oral glucose tolerance tests carried out with glucose-loaded mice. The extracts at different doses were administered one hour prior to glucose administration and blood glucose level was measured after two hours of glucose administration (p.o.) using glucose oxidase method. Significant oral hypoglycemic activity was found with the extracts of leaves of all three plants tested. The fall in serum glucose levels were dose-dependent for every individual plant, being highest at the highest dose tested of 400 mg extract per kg body weight. At this dose, the extracts of A. carambola, F. hispida, and S. samarangense caused, respectively, 34.1, 22.7, and 59.3% reductions in serum glucose levels when compared to control animals. The standard antihyperglycemic drug, glibenclamide, caused a 57.3% reduction in serum glucose levels versus control. Among the three plants evaluated, the methanolic extract of leaves of S. samarangense proved to be the most potent in demonstrating antihyperglycemic effects. The result validates the folk medicinal uses of A. carambola and F. hispida in the treatment of diabetes, and indicates that the leaves of S. samarangense can also possibly be used for amelioration of diabetes-induced hyperglycemia.